2D Covalent Organic Framework for Water Harvesting with Fast Kinetics and Low Regeneration Temperature. Issue 11 (31st January 2023) - Sun, Chao; Zhu, Yuhao; Shao, Pengpeng; Chen, Liwei; Huang, Xin; Zhao, Shuang; Ma, Dou; Jing, Xuechun; Wang, Bo; Feng, Xiao
Abstract: Atmospheric water harvesting represents a promising technique to address water stress. Advanced adsorbents have been rationally designed to achieve high water uptake, yet their water sorption kinetics and regeneration temperature greatly limit water production efficiency. Herein, we demonstrated that 2D covalent organic frameworks (COFs), featuring hydrophobic skeleton, proper hydrophilic site density, and 1D open channels significantly lowered the water diffusion and desorption energy barrier. DHTA‐Pa COF showed a high water uptake of 0.48 g/g at 30 % R.H. with a remarkable adsorption rate of 0.72 L/Kg/h (298 K) and a desorption rate of 2.58 L/Kg/h (333 K). Moreover, more than 90 % adsorbed water could be released within 20 min at 313 K. This kinetic performance surpassed the reported porous materials and boosted the efficiency for multiple water extraction cycles. It may shed light on the material design strategy to achieve high daily water production with low‐energy input. Abstract : Exceptional water adsorption/desorption dynamic properties and low regeneration temperature were achieved by 2D covalent organic frameworks (COFs) with 1D open channels and alternatively arranged hydrophilic/hydrophobic segments. It is promising for improving cycle efficiency and lowering the energy consumption in the atmospheric water harvesting processes.